Gaze shift patterns in gymnasts during a jump with a half turn - Sato, Y.; Torii, S.; Sasaki, M. (Japan Journal of Physical Education, Health and Sport Sciences, 2016)
This study aimed to clarify gaze shift patterns in gymnasts during a jump with a half turn by measuring horizontal eye-head movements. We also compared the gaze shift patterns of skilled gymnasts with those of non-gymnasts to examine the patterns characteristic of gymnasts. The participants were 10 skilled male gymnasts and 15 male non-gymnasts. Each participant performed a jump with a half turn, which is an aerial movement with a 180-degree longitudinal axis rotation. Eye movement during the jump was measured using electrooculography. The jump was recorded simultaneously with 2 high-speed digital cameras to determine angular horizontal head movement. Gaze was determined by combining eye and head movement data. The results showed that both gymnasts and non-gymnasts used 2 gaze shift patterns during the jump. In both of these patterns, gaze stabilized before takeoff and immediately before landing. However, in one pattern, termed the single-step gaze shift pattern, gaze moved directly from front to back, whereas in the other pattern, termed the multi-step gaze shift pattern, gaze shift toward the direction of rotation stopped several times even during midair rotation. The single-step gaze shift pattern was used more by gymnasts than by non-gymnasts. Taken together, these results show that gymnasts employ 2 gaze shift patterns when performing a jump with a half turn, but that the single-step gaze shift pattern may be more useful to gymnasts for controlling their movement than other gaze shift patterns.